Status and scope of project management in the hospitality industry. Issue 2 (28th October 2019) - Rengel Jara, Eduardo Vicente; Babb, Jackson Wayne; Flohr, Timothy Marshall
Abstract : Purpose: Project management is an essential skill in the hospitality organization that is only becoming more important (Tereso et al., 2019 ). Bridging the gap between academia and industry is achievable by experiential learning or providing students with curriculum that gives them hands-on access to real-world industry research projects that attempt to solve real-world industry issues (Steed and Schwer, 2003 ). The purpose of this paper is to understand the scope of project management curriculum in universities' hospitality programs, to understand the scope of project management skill requirements in hospitality firms and to narrow the disconnect between project management in academia and in hospitality firms. Design/methodology/approach: The study used a mixed method approach. On the side of academia, a quantitative collection method was used to gage which universities offered a project management course, how many universities offer these courses and how many project management courses each university had. On the side of industry, a survey was administered to industry professionals in senior management positions. It was a quantitative survey designed to gage the importance of having project management as part of university curriculum. The aim was to show what was expected to be a disconnect between the two sides – academia and industry. A total of 57 responses were collected. Out of them 49 were usable. The Human Subjects consisted solely of two populations: individuals who worked in the hospitality industry. This accounted for 12 of the responses; individuals who worked in academia – more specifically in higher education at schools that offer Hospitality Management curriculum. This accounted for 37 of the responses. The subjects were identified and recruited through the professional networking site LinkedIn (for subjects that were industry professionals) and through both LinkedIn and American Hotel Lodging and Educational Institute databases for the subjects in academia. There were no direct potential benefits to the subject. The potential societal benefits of the study were the advancement of knowledge within the disciplines of both Hospitality Management and Project Management. The authors used the University of Memphis' Qualtrics system and changed settings to anonymize responses so IP addresses would not be collected. The Qualtrics' default is to collect IP addresses and GPS coordinates of those who responded. By setting the survey to anonymized responses the investigators were not able to collect this identifiable information. This information was included in the confidentiality, methods/procedures and in any other necessary sections/documents noting that the investigators would set Qualtrics to anonymize responses. Findings: H1 was supported. The findings showed that most colleges and universities did not require project management classes for degree completion. Preliminary research showed that of 68 of the top hospitality programs in the world that were researched, only 7.5 percent required taking project management centric courses in order to graduate (College Choice, 2019 ; The Best Schools, 2019 ; Top Universities, 2018 ). In total, 43.2 percent of respondents answered "yes" when asked if their school offers courses in project management based on this definition of project management: "A project is temporary in that it has a defined beginning and end in time, and therefore the defined scope and resources. And a project is unique in that it is not a routine operation, but a specific set of operations designed to accomplish a singular goal. A project team often includes people who do not usually work together – sometimes from different organizations and across multiple geographies. Project management, then, is the application of knowledge, skills, tools, and techniques to project activities to meet the project requirement" (Project Management Institute) (See Table A1). Of 43.2 percent that answered yes, 64.3 percent said that the courses were required for graduation (See Table AII). Meaning, only 27.8 percent of schools surveyed offered and required completing project management courses for graduation. It should be noted that this number may be lower as bias may have played a factor. It is evident that hospitality programs understand the importance of project management because 85.7 percent of the colleges and universities surveyed are teaching project management concepts in courses that are not project management centric, like Meeting and Event Planning (See Table AIII). H2 was supported. Only 9.1 percent of respondents believed that project management skills are not at all important to line level employees. Most, 54.6 percent, believed that project management skills are important to some extent for line level employees. In total, 9.1 percent believed that project management skills are not at all important for supervisory level employees; 27.3 percent believed they are needed to some extent and 36.4 percent believed they are needed to a moderate extent. As for management level employees, it was found that 63.6 percent believed project management skills were needed to a great extent. For director level employees, 63.6 percent believed project management skills are necessary. Finally, 72.7 percent of respondents believed project management skills are necessary for both VP level employees and executive leadership (See Table AIV). It should be noted that one person did not believe themselves qualified to answer questions regarding project management within their organization. More than half of respondents said that project management skills are used to a great extent within their organization. H3 was not supported. Both hospitality schools and hospitality companies agreed that project management skills have some level of importance in academia and in industry – most believed the skills were very important at both junctions (See Tables AV and AVI). However, in the preliminary research the authors found that 55 percent of the top 111 hospitality companies had project management positions, meaning that there was a potential need for project management courses in colleges and universities (Ranker, 2019 ). As stated earlier, only 7.5 percent of the top 68 colleges and universities required project management courses to be completed upon graduation. So, the discrepancy lies within the vastly different percentages between project management positions within companies and project management courses within schools. Research limitations/implications: The data provided strong evidence that supported the idea that project management is not required in hospitality programs upon completion. This opens new avenues to research the reasons behind schools not offering project management courses or making it a requirement for degree completion. On the other hand, project management skills are considered to be needed by hospitality managers. This provides valuable information for future studies that look to close the gap between academia and industry. The results indicated that project management is important for hospitality companies and schools, but the lack of project management education in colleges and universities is evident. The results of this study provided good news to students that aim to work in hospitality companies, since they can improve their project management skills and encourage their programs to stay updated with the industry needs so that they can succeed in their professional lives. Though this was an exploratory study of the project management discipline within the hospitality industry – with a limited sample size – the data clearly justified that there is room for additional data collection and research in this area of study. Practical implications: The results show that there is a disconnect between project management curriculum in schools and project management skill demand in the hospitality industry. The research should encourage schools to invest appropriate resources into required project management curriculum. The hospitality industry is vast in the types of businesses that fall under it. Project management is one skill set that can be useful across most of the different businesses in the hospitality industry. From a practical standpoint, providing students with a solid background in the project management discipline provides them an advantage in the highly competitive hospitality industry. It accomplishes this by providing the students with in-demand knowledge and competencies that are both universally accepted and highly regarded by hospitality management companies as a skill set that is widely used in the industry. Social implications: There were limitations to this study. Some pieces may be improved in future research. The Qualtrics survey could have been reduced in number and order of questions for a better interaction and results. The use of the Qualtrics database might be helpful to reach a bigger population. Potential steps could be taken to reduce bias that may play a factor in the responses. For example, some respondents may have claimed that their schools offer project management curriculum when in fact they do not, or they do not know to what extent. Originality/value: Project management is an essential skill in the hospitality organization that is only becoming more important (Tereso et al., 2019 ). Bridging the gap between academia and industry is achievable through experiential learning or providing students with curriculum that gives them hands-on access to real-world industry research projects that attempt to solve real-world industry issues (Steed and Schwer, 2003 ). Most graduate level curriculum at universities was found to hone skills like written and oral communications, problem solving and decision making, organization, time management and cost control (Steed and Schwer, 2003 ). It has been suggested that universities add project management curriculum and experiential learning to their programs for a more streamlined transition from academia to industry (Steed and Schwer, 2003 ). Existing research on this subject is a bit dated, so the objectives were: to understand the scope of project management curriculum in universities' hospitality programs; to understand the scope of project management skill requirements in hospitality firms; to narrow the disconnect between project management in academia and in hospitality firms.